Спорудження фундаментів оперного театру у м. Львові - Холод, П. Ф.; Гнатюк, О. Т.; Лапчук, М. А.; Мазурак, А. В.; Kholod, P. F.; Hnatiuk, O. T.; Lapchuk, M. A.; Mazurak, A. V. (Видавництво Львівської політехніки, 2019)
Будівництво оперного театру у Львові стало однією з найважливіших подій у культурному і громадському житті міста. У 1895 році після тривалих дискусій було оголошено конкурс на кращий проект нової театральної споруди. Компетентне журі обрало переможця, яким виявився архітектор Зигмунт Горголевський. У 1886 році йому було доручено керівництво будівництвом театру. На початку будівництва гостро постало питання фундаментів. Для визначення технічної придатності на проектованій ділянці були викопані шурфи та проведене випробування ґрунтів статичним навантаженням. Після аналізу результатів випробувань було запроектовано стрічкові бетонні фундаменти так, щоби рівномірно розподілений тиск на ґрунт під ними не перевищував 1,5 кг/см2. Земляні роботи для фундаменту нового театру розпочали 5 червня, бетонування плит фундаментів тривало від 21 серпня до середини жовтня 1897 року. Через рік почали закладати фундаменти, для чого було відведено русло Полтви.

The construction of the opera house in Lviv has become one of the most important events in the cultural and public life of the city. The rapid socio-economic development of Galicia and Lviv at the end of the 19th century contributed to the appearance of this architectural jewel of the city. It was at that time that there was a tangible need to build a large city theater. In 1895, after long discussions, a competition for the best project of a new theatrical construction was announced. The competent jury chose the winner, which turned out to be the architect Sigmund Gorgolevsky. The winner pleasantly surprised the jury choosing a place to build – in the city center, although it was then tightly built up and offered to hide the underground Poltva River, which proceeded in this place. In 1986, he was entrusted with the leadership of the construction of the theater. At the beginning of construction, the question of foundations was acute. When the site for the theater was almost determined, it was necessary to make sure it was technically fit for construction. To do this, at the projected site, pits were excavated and soil tests conducted with static loading. After analyzing the test results, the tape concrete foundations were designed in such a way that evenly distributed pressure on the soil below them did not exceed 1,5 kg/cm2. The bottom of concrete pillows should have been at the same level as the whole house, dictated by the depth of the premises under the stage, and they should be based exclusively on the natural basis. Earthworks for the foundation of the new theater began on June 5, concrete concreting of the basement plates lasted from August 21 to mid-October 1897. A year later, the laying of foundations began, which led to the removal of the bed of Poltva. During construction many difficulties arose, but on October 4, 1900, the Lviv Opera House was officially opened with the opening ceremony of the opera Janek V. Zhelensky.
Construction of opera house foundations in Lviv
Keywords: стрічкові бетонні фундаменти; випробування ґрунтів статичним навантаженням; tape concrete foundations; soil tests with static loading; 624.153.5